2007
DOI: 10.1111/j.1442-2050.2007.00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Transabdominal ligation of the thoracic duct as treatment of choice for postoperative chylothorax after esophagectomy

Abstract: Postoperative chylothorax after injury of the thoracic duct during esophagectomy is a rare but severe complication which may lead to serious problems such as loss of fat and proteins, and immunodeficiency. Without treatment mortality can rise to over 50%. From 1988 to 2005, we treated 10 patients with postoperative chylothorax after 409 resections of the esophagus (2.4%). Of these 10 patients nine underwent transthoracic esophagectomy with gastric pull-up to enable an intrathoracic (n = 7) or cervical (n = 2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 32 publications
1
27
0
2
Order By: Relevance
“…If chyle is not stopped, patients will faced immune deficiency, resulting in infection and mortality (35). Some studies have shown the superiority of surgery over conservative treatment (34,(38)(39)(40). Thus, the treatment method of Chylothorax is conservative but when the outlet of the chest tube is more than 800 cc per day and it will continue for 4 to 5 consecutive days, waiting for stopping the leak may be dangerous due to leukopenia and malnutrition; therefore, surgery is required in these circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…If chyle is not stopped, patients will faced immune deficiency, resulting in infection and mortality (35). Some studies have shown the superiority of surgery over conservative treatment (34,(38)(39)(40). Thus, the treatment method of Chylothorax is conservative but when the outlet of the chest tube is more than 800 cc per day and it will continue for 4 to 5 consecutive days, waiting for stopping the leak may be dangerous due to leukopenia and malnutrition; therefore, surgery is required in these circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of chylothorax in transhiatal esophagectomy ranges from 0.6 % to 10.5 % [1][2][3]. Due to this low incidence, there is very few evidence on its predisposing factors and its optimal treatment of choice.…”
Section: Introductionmentioning
confidence: 93%
“…[4][5][6][7] Chylous pleural effusions are typically described as exudative lymphocytic pleural effusions with a milky appearance. However, biochemical parameters of chylous pleural effusions have been inadequately analyzed.…”
Section: © 2009 Mayo Foundation For Medical Education and Researchmentioning
confidence: 99%